2009
DOI: 10.24820/ark.5550190.p003.774
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of 5-carboxanilide-dihydropyrimidinones using etidronic acid

Abstract: A combination of a modified Biginelli reaction and an etidronic acid prompted a cyclocondensation reaction providing 5-carboxanilide-dihydropyrimidinones in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Dihydropyrimidinones 29 (69%-97% yield) were achieved by Pansuriya and colleagues via the reaction of N -phenyl-3-oxobutanamides 28 with urea 8 and aldehydes 21 in the presence of etidronic acid (Scheme 5). 20 Etidronic acid was found suitable for all types of aldehydes and provided good to excellent yields of products compared to PPA and PPE.…”
Section: Multicomponent Synthesismentioning
confidence: 95%
“…Dihydropyrimidinones 29 (69%-97% yield) were achieved by Pansuriya and colleagues via the reaction of N -phenyl-3-oxobutanamides 28 with urea 8 and aldehydes 21 in the presence of etidronic acid (Scheme 5). 20 Etidronic acid was found suitable for all types of aldehydes and provided good to excellent yields of products compared to PPA and PPE.…”
Section: Multicomponent Synthesismentioning
confidence: 95%
“…More recently, in a number of works [ 40–42 ] it was found that etidronic acid (HEDP) proved to be a convenient “green” catalyst in 3‐component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [ 40,41 ] and under microwave synthesis. [ 42 ] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2‐dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, we have been involved in a program aimed at exploring the synthetic potential of 3-oxobutanamide derivative 1 as building blocks for polyfunctionally substituted hetero-aromatics. [1][2][3][4][5][6][7] Heterocyclic compounds possess a wide variety of important biochemical effects and pharmacological properties. Most of the heterocyclic Compounds are containing nitrogen, oxygen and sulfur possess broad spectrum of biological activity such as anti-bacterial and anti-fungal, [8,9] antiviral, [10] anti-inflammatory, [11] and anti-tumor drugs.…”
Section: Introductionmentioning
confidence: 99%